Rapid melt growth of crystalline germanium for solar energy harvesting applications - Zainal, Nurfarina (2014)
Recent development of energy conversion devices namely photovoltaic (PV) cells or solar cells and thermophotovoltaic (TPV) cells require the use of bulk germanium as substrate material for efficient device performance. Germanium is employed in solid-state terrestrial or space energy conversion devices due to its excellent electrical properties. With a bandgap of 0.66 eV, energy from infrared region of solar or thermal spectrum can be absorbed and converted into electrical energy. At present, multi-junction solar cells with bulk germanium substrates show the highest performance but have complex and expensive manufacture processes. The major contributor to the high cost is the germanium substrate, which is an expensive and scarce material. One of the possibilities to reduce cost is by using thin film instead of thick bulk germanium. To date, development of thin film germanium for energy conversion devices has not been established. By providing germanium on insulator structures a good quality thin film germanium can be attained and thus, offer a low cost route. The rapid melt growth (RMG) technique has been proposed, where it potentially produces thin film germanium with quality similar to that of bulk material. In the existing RMG technology germanium thickness has been limited to 100 nm. For photovoltaic applications thicker germanium films are required to increase energy absorption for eficient performance. For these reasons, alternative RMG routes to producing thin films for energy conversion devices have been investigated. The feasibility and efficacy of the RMG technique has been evaluated for different germanium deposition methods namely physical vapour deposition (PVD) and chemical vapour deposition (CVD). In this study, a novel RMG technology has been established in order to produce high quality thick germanium films (above 100 nm). Experiments have been conducted with various anneal temperature, germanium patterns, substrate and crucible materials to achieve optimum crystalline quality. Micro-Raman spectroscopy has shown that the technology has the capability to produce thick germanium films that are free from major defects such as cracks and delamination, with crystalline quality similar to that of bulk material. This thesis highlights the use of PVD germanium compared to CVD germanium in minimising silicon diffusion through the crystal growth process, which has resulted in longer length of crystal germanium. The mechanism of germanium lateral crystallisation has been investigated in this thesis by depositing germanium onto non-silicon substrates. A prototype germanium photovoltaic has been fabricated to demonstrate the potential of the RMG technique in production of future solar cells.